Does green tea catechin enhance weight-loss effect of exercise training in overweight and obese individuals? a systematic review and meta-analysis of randomized trials - Farhad Gholami; Jose Antonio; Mohadeseh Iranpour; Jason Curtis; Flavia Pereira (Journal of the International Society of Sports Nutrition)
Background Green tea (GT) is a common component of supplements known as fat burners. It has gained popularity as an ergogenic aid for weight reduction to assist with obesity management. This systematic review and meta-analysis aim to explore the effect of green tea ingestion coupled with exercise training (EX) on body composition and lipid profile in overweight and obese individuals.Methods Two independent researchers systematically searched the electronic databases of PubMed, Web of Science, and Scopus. Studies with a randomized-controlled design to compare the effect of green tea in conjunction with exercise training (EX+GT) versus exercise training alone (EX+P) in overweight or obese participants were included.Results Of the 1,015 retrieved studies, 24 were identified to undergo full-text review, out of which 10 randomized trials met the inclusion criteria. EX+GT versus EX+P had a small and consistent effect on weight [Standardized mean difference (SMD) = -0.30, CI: −0.53 to −0.07], BMI [SMD = -0.33 CI: −0.64 to −0.02] and fat reduction [SMD = -0.29, CI: −0.57 to −0.01] and there was no evidence of heterogeneity across the trials. When compared to EX+P, EX+GT had no greater effect on lipid profile improvement [triglyceride: SMD = -0.92, CI: −1.30 to 0.49; LDL: SMD = -1.44, CI: −0.73 to 0.82; HDL: SMD = 0.56, CI −0.71 to 0.46; and total cholesterol SMD = -0.54, CI −0.85 to 0.13].Conclusions Current evidence suggests that green tea could have quite minimal additive benefit over exercise-induced weight loss. However, incorporation of green tea into exercise training does not seem to exert additional benefits on lipid profile and it warrants further investigations in the future.